COMBINED COMPOSITE REINFORCED CONCRETE BEAMS - Umarov Shodiljon Abdugоfurovich; Mirzababaeva Sakhiba Mirzaakbarovna; Solijonov is the son of Foziljan Sadiqjan; Mirzayeva is the daughter of Zarnigor Alisher (Journals Park Publishing, 2022)
This article describes the analysis of the results of the research conducted on the study of the work of composite reinforced elements, which are widely used in the restoration of concrete structures in the buildings and structures currently being built in the Republic of Uzbekistan and in foreign countries.
Keywords: composite, basalt, concrete, flexibility, strength, messura, polymer